ETHOS, PATHOS, AND LOGOS IN CORPORATE PRESENTATIONS: A RESEARCH CASE STUDY OF THE FIRST IPHONE LAUNCH PRESENTATION - Trivedi, Kaushik; Brahmkshatri, Chandrakant Y.; Purohit, Divyang (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The present research paper is an examination of the rhetorical methods that were used by Steve Jobs when launching the first iPhone at the Macworld Conference and Expo 2007 on January 9, 2007. The presentation is commonly seen as one of the most influential product launches in the corporate history since it was a mixture of technological innovation and the outstanding use of persuasive communication. This research employs the qualitative case study research design and applies the classical rhetorical system of ethos, pathos and logos to the presentation style, speech structure, visual design, and audience engagement strategies used by Jobs. The data was elicited by launch transcripts, video recordings, published commentary, and scholarly literature on rhetoric and business communication. Results show that Jobs was strategic in establishing credibility by using the reputation of Apple as well as his own persona, created emotional excitement by using suspense, humor and visionary language, and supported claims logically through live demonstrations and comparative reasoning. Other devices like repetition, contrast, storytelling and minimalist slides further enhanced the persuasive power. The paper theorizes that effective corporate presentations are not only based on the quality of products, but also on the framing of the story, the psychology of the audience, and the rhetorical performance. Furthermore, the paper will consider how Jobs kept the design of his slides to a minimum and how he always made time to slow down his speech in order to maximize the convincing effect of his words. Breaking down these components, the study will help to shed some light on successful strategies of public speaking that can be implemented in different fields. Learning the rhetorical strategy used by Jobs can provide useful lessons to professional, business leaders, marketing managers, and presenters aiming to influence and motivate their audiences, consumers, media, and presenters. The paper concludes that the launch of the iPhone by Steve Jobs is a lasting example of how leaders, educators, entrepreneurs, marketers, and professionals can use to communicate innovation successfully in competitive markets.